BUILDING FINANCIAL INDEPENDENCE FOR ORIGINAL CHILDREN THROUGH TRAINING OF MERANG MUSHROOM (Volvariella volvacea) - Nursyahra Nursyahra; Febri Yanti (Universitas PGRI Sumatera Barat, 2021)
Entrepreneurial development in Indonesia is still limited. The phenomenon in Indonesia is that the majority of high school graduates (61.88%) prefer to be employees rather than being entrepreneurs. In line with this, it is necessary to have entrepreneurship training from an early age to community groups such as orphans. Providing entrepreneurial training for orphanage children because they need to have the skills to train an independent spirit in addition to training financial independence from an early age in children. Based on the above background, a dedication was carried out on Building Financial Independence for Children at LKSA Orphanage Al Hidayah Padang Orphanage through Training for Cultivation of Straw Mushrooms (Volvariella volvacea). Mushrooms can grow on waste media, because fungi are able to degrade organic waste. With this ability, mushrooms can be used to add value to waste. Waste that can be converted into a mushroom growing medium is rice straw, but the straw needs to go through a composting process first. Mushrooms are included in the saprophytic fungus group, namely fungi that grow on organic substrates from dead animals and plants and convert the substrate into substances that are easily absorbed. This service is also expected to increase students' knowledge and knowledge so that they can motivate them to open their own jobs without having to depend on others and also be expected to be an example for others. Besides, it is hoped that with the completion of this service, it can increase the child's care for the environment by being able to utilize the wasted waste and produce something useful.